ВИТАМИНЫ В ПИТАНИИ ГИМНАСТОВ - Ешбаев, А.Ж.; Акимов, Н.Т. (SCIENCE and SOCIETY, 2017)
The article deals with the nutrition of gymnasts and it contains wide data about the roles of vitamins. The rattional nutrition is very important in training and restoration of organizm.
Keywords: gymnast; nutrition; vitamins; minerals; calorie; proteins; fat; metabolism